Headbanging in Taiwan. (1st June 2017) - Chiu, Hsiang; de Seta, Gabriele
Drawing on the authors' sustained immersion and participation in local music scenes, this short article lays the groundwork for Taiwanese metal music studies. Heavy metal music arrived in Taiwan in the early 1980s through the precarious mediation of daoban [pirated] tapes and foreign television channels and, in the course of three decades, it has moved from a niche and hardly accessible genre to an established ensemble of scenes, subgenres, bands, venues, record labels, booking agencies, distributors, rehearsal spaces and audiences. After sketching a history of metal music in Taiwan in dialogue with a local record distributor, the authors describe how a subgenre such as death metal is practiced, discussed and sustained – through equipment, skills and judgments – during a few hours of a local band's rehearsal. In light of the history, development and practice of metal music in Taiwan, more research about local bands, audiences and scenes appears urgent and necessary.